Insourcing the war-economy: Building a resilient Ukraine means maximising its domestic output - Cooper, Luke (My University, 2023)
Markets cannot function in wartime; the Ukrainian state therefore needs to embrace its inevitably central role as the coordinator of an integrated war-economy. This policy brief argues that the Government of Ukraine should pursue policies that prioritise Ukraine’s economic resilience and mitigate against the risk of balance of payments crisis, in the event that there is a significant reduction in donor support. PeaceRep’s Ukraine programme is involved in providing analysis, evidence and data to prepare discussions at the London Ukraine Recovery Conference, 21 – 22 June 2023. As part of this work, this policy brief presents findings from meetings in Kyiv with government officials, civil society activists, trade unions, and academics, as well as visits to industrial sites in the Kyiv Oblast region.
Keywords: Conflict Management; Ukraine